Retinal ganglion cell-inner plexiform layer, white matter hyperintensities, and their interaction with cognition in older adults - Wang, Ruilin; Wu, Xinmao; Zhang, Zengyi; Cao, Le; Kwapong, William Robert; Wang, Hang; Tao, Wendan; Ye, Chen; Liu, Junfeng; Wu, Bo (Frontiers in Aging Neuroscience, 2023)
We explored the interaction of optical coherence tomography (OCT) parameters and white matter hyperintensities with cognitive measures in our older adult cohort.Methods: This observational study enrolled participants who underwent a comprehensive neuropsychological battery, structural 3-T brain magnetic resonance imaging (MRI), visual acuity examination, and OCT imaging. Cerebral small vessel disease (CSVD) markers were read on MR images; lacune, cerebral microbleeds (CMB), white matter hyperintensities (WMH), and enlarged perivascular spaces (EPVS), were defined according to the STRIVE standards. Retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform layer (GCIPL) thicknesses (µm) were measured on the OCT tool.Results: Older adults with cognitive impairment (CI) showed lower RNFL (P = 0.001), GCIPL (P = 0.009) thicknesses, and lower hippocampal volume (P = 0.004) when compared to non-cognitively impaired (NCI). RNFL (P = 0.006) and GCIPL thicknesses (P = 0.032) correlated with MoCA scores. GCIPL thickness (P = 0.037), total WMH (P = 0.003), PWMH (P = 0.041), and DWMH (P = 0.001) correlated with hippocampal volume in our older adults after adjusting for covariates. With hippocampal volume as the outcome, a significant interaction (P < 0.05) between GCIPL and PWMH and total WMH was observed in our older adults.Conclusions: Both GCIPL thinning and higher WMH burden (especially PWMH) are associated with hippocampal volume and older adults with both pathologies are more susceptible to subclinical cognitive decline.